Large golden-ringed dragonfly Cordulegaster heros Theischinger 1979, new for the fauna of Italy (Odonata: Cordulegastridae) - Matjaž Bedjanič; Ali Šalamun (Natura Sloveniae)
The species has been recorded at three localities in the extreme eastern part of the Friuli-Venezia Giulia region, north-eastern Italy, thus bringing the number of Italian dragonfly species to 89. The distribution of C. heros in Slovenia and Italy is mapped and discussed from the zoogeographical point of view. Additionally, the collected faunistic data on other dragonfly species and sympatric occurrence of endangered frog species Rana latastei Boulenger are given. Due to inclusion of C. heros and R. latastei to the Annexes II and IV of the Habitat Directive of EU, the conservation of their habitats in Italy and western Slovenia is proposed within the European network of protected areas NATURA 2000.